Jödisk undervisning. Litt om skolen i Israel og om ulike nyere jödiske undervisningsopplegg - Rian, Gyda Birkeland (Nordisk judaistik, 1983)
The first part of this article gives a short historical survey of education and the school system in Palestine since the 19th century. After 1948 preparation of school legislation was given high propriety in Israel. Education should be based on Jewish culture and values. Israel had some challenges because of the enormous immigration after 1948. These problems of course affect the school, which has had difficulties in finding qualified teachers, in giving equal education in all areas, in providing the kind of education the State needs for a great number of students. Trying to give the sabras an identity, the state started a "Jewish Consciousness programme" which put Jewish culture and religion in focus. The second part of the article gives a survey of various teaching programmes for primary and secondary school. The projects described are one in history, one about immigration to Israel in the period from 1850 till today, and one in language and literature. The Curriculum Centre in Jerusalem coordinates all these projects, gives help to the teachers and supplies the schools with materials.